Tìm x:
2. (70 + x) + 2^3 . 3^2 = 92
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(70-\left(x-3\right)=45\)
\(x-3=70-45\)
\(x-3=25\)
\(x=25+3\)
\(x=28\)
b) \(12+\left(5+x\right)=20\)
\(5+x=20-12\)
\(5+x=8\)
\(x=8-5\)
\(x=3\)
c) \(130-\left(100+x\right)=25\)
\(100+x=130-25\)
\(100+x=105\)
\(x=105-100\)
\(x=5\)
d) \(175+\left(30-x\right)=200\)
\(30-x=200-175\)
\(30-x=25\)
\(x=30-25\)
\(x=5\)
e) \(\left(x+12\right)+22=92\)
\(x+12=92-22\)
\(x+12=70\)
\(x=70-12\)
\(x=58\)
f) \(95-\left(x+2\right)=45\)
\(x+2=95-45\)
\(x+2=50\)
\(x=50-2\)
\(x=48\)
a)
70 - (x - 3) = 45
x - 3 = 70 - 45 = 25
x = 25 + 3 = 28
Vậy x = 28
b)
12 + (5 + x) = 20
5 + x = 20 - 12 = 8
x = 8 - 5 = 3
Vậy x = 3
c)
130 - (100 + x) = 25
100 + x = 130 - 25 = 115
x = 115 - 100 = 15
Vậy x = 15
d)
175 + (30 - x) = 200
30 - x = 200 - 175 = 25
x = 30 - 25 = 5
Vậy x = 5
e)
(x + 12) + 22 = 92
x + 12 = 92 - 22 = 70
x = 70 - 12 = 58
Vậy x = 58
f)
95 - (x + 2) = 45
x + 2 = 95 - 45 = 50
x = 50 - 2 = 48
Vậy x = 48
ĐKXĐ:...
a. Đặt \(\left\{{}\begin{matrix}\sqrt{2x^2+4x+16}=a>0\\\sqrt{x+70}=b\ge0\end{matrix}\right.\)
\(\Rightarrow6x^2+10x-92=3a^2-2b^2\)
Pt trở thành:
\(3a^2-2b^2+ab=0\)
\(\Leftrightarrow\left(a+b\right)\left(3a-2b\right)=0\)
\(\Leftrightarrow3a=2b\)
\(\Leftrightarrow9\left(2x^2+4x+16\right)=4\left(x+70\right)\)
\(\Leftrightarrow...\)
b. ĐKXĐ: ...
Đặt \(\left\{{}\begin{matrix}\sqrt{x+1}=a\ge0\\\sqrt{1-x}=b\ge0\end{matrix}\right.\)
Phương trình trở thành:
\(a^2+2+ab=3a+b\)
\(\Leftrightarrow a^2-3a+2+ab-b=0\)
\(\Leftrightarrow\left(a-1\right)\left(a-2\right)+b\left(a-1\right)=0\)
\(\Leftrightarrow\left(a-1\right)\left(a+b-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}a=1\\a+b=2\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{x+1}=1\\\sqrt{x+1}+\sqrt{1-x}=2\end{matrix}\right.\)
\(\Leftrightarrow...\)
1) \(\dfrac{1}{4}x-\dfrac{1}{3}=\dfrac{-5}{9}\)
\(\Rightarrow\dfrac{1}{4}x=-\dfrac{2}{9}\Rightarrow x=-\dfrac{8}{9}\)
2) \(2^{x-3}-3.2^x=-92\)
\(\Rightarrow2^x\left(2^{-3}-3\right)=-92\)
\(\Rightarrow2^x.\dfrac{-23}{9}=-92\)
\(\Rightarrow2^x=32\Rightarrow x=5\)
1)
\(4x^2-4x+1-4x^2-16x-16=9\)
\(-20x-15=9\)
-20x=24
x=-1,2
3)
(2x+1)2=52
2x+1=5
2x=4
x=2
\(1,\Rightarrow4x^2-4x+1-4x^2-16x-16=9\\ \Rightarrow-20x=23\Rightarrow x=-\dfrac{23}{20}\\ 2,\Rightarrow9x^2-6x+1+2x+6+11-11x^2=15\\ \Rightarrow2x^2+4x-3=0\\ \Rightarrow2\left(x^2+2x+1\right)-5=0\\ \Rightarrow2\left(x+1\right)^2-5=0\\ \Rightarrow\left[\sqrt{2}\left(x+1\right)-\sqrt{5}\right]\left[\sqrt{2}\left(x+1\right)+\sqrt{5}\right]=0\\ \Rightarrow\left[{}\begin{matrix}\sqrt{2}\left(x+1\right)=\sqrt{5}\\\sqrt{2}\left(x+1\right)=-\sqrt{5}\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x+1=\sqrt{\dfrac{5}{2}}=\dfrac{\sqrt{10}}{2}\\x+1=-\sqrt{\dfrac{5}{2}}=\dfrac{-\sqrt{10}}{2}\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=\dfrac{\sqrt{10}-2}{2}\\x=\dfrac{-\sqrt{10}-2}{2}\end{matrix}\right.\)
\(3,\Rightarrow\left(2x+1\right)^2-25=0\Rightarrow\left(2x+1-5\right)\left(2x+1+5\right)=0\\ \Rightarrow\left[{}\begin{matrix}2x=4\\2x=-6\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=2\\x=-3\end{matrix}\right.\)
\(4,\Rightarrow x^3+3x^2+3x+1-x^3-2x^2-2x+1-x^2=15\\ \Rightarrow x+2=15\Rightarrow x=13\)
a) \(92.4-27=\frac{x+350}{x}+315\)
\(368-27=1+\frac{350}{x}+315\)
\(341=\frac{350}{x}+316\)
\(341-316=\frac{350}{x}\)
\(25=\frac{350}{x}\)
\(25x=350\)
\(x=14\)
b) \(\left(\frac{3}{2}-x\right).\frac{1}{3}-\frac{2}{3}.\left(\frac{1}{2}-x\right)=\frac{1}{3}\)
\(\frac{\frac{3}{2}}{3}-\frac{x}{3}-\frac{2}{3}.\left(\frac{1}{2}-x\right)=\frac{1}{3}\)
\(\frac{1}{2}-\frac{x}{2}-\frac{2}{3}.\left(\frac{1}{2}-x\right)=\frac{1}{3}\)
\(\frac{3}{2}-x-2.\left(\frac{1}{2}-x\right)=1\)
\(\frac{3}{2}-x-1+2x=1\)
\(\frac{1}{2}+x=1\)
\(x=1-\frac{1}{2}\)
\(x=\frac{1}{2}\)
2:
1: =>36x+14x=69+81=150
=>50x=150
=>x=3
2: 3^x=81
=>3^x=3^4
=>x=4
3: 3(2x+1)^2=75
=>(2x+1)^2=25
=>2x+1=5 hoặc 2x+1=-5
=>x=-3 hoặc x=2
1:
1: \(\dfrac{13\cdot17^4+4\cdot17^4}{17^3}-\dfrac{14\cdot3^3-14\cdot3^2}{9}\)
\(=\dfrac{17^4\cdot\left(13+4\right)}{17^3}-\dfrac{14\cdot3^2\left(3-1\right)}{9}\)
\(=17\cdot17-14\cdot2\)
=289-28
=261
2:
\(2^3\cdot5^2-\left[131-\left(23-2^3\right)^2\right]\)
\(=8\cdot25-131+\left(-1\right)^2\)
=69+1
=70
\(2.\left(70-x\right)+2^3.3^2=92\)
\(140-2x+72=92\)
\(-2x=92-212\)
\(-2x=-120\)
\(x=60\)
\(a,12\left(x-1\right)=0\\ x-1=0\\ x=1\\ b,45+5\left(x-3\right)=70\\ 5\left(x-3\right)=25\\ x-3=5\\ x=8\\ c,3.x-18:2=12\\ 3.x-9=12\\ 3.x=21\\ x=7\)
( 70 + x ) + 8.9 = 92
( 70 + x ) + 72 = 92
70 + x = 92 - 72
70 + x = 20
x = 20 - 70
x = -50
2( 70 + x ) + 8.9 = 92
2( 70 + x ) + 72 = 92
2( 70 + x ) = 92 - 72
2(70 + x ) = 20
70 + x = 20 : 2
70 + x = 10
x = 10 - 70
x = -60